Peran Pengawas Sekolah Dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Inpres Kolongan Atas Kecamatan Sonder - Jemry Agustinus Amstrong Langie (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of writing this article is to describe the role of school supervisors in improving the quality of education. This article was written using the method of literature review and content analysis. A literature review was conducted to reveal various theories and information relevant to the topic under study, namely the role of school supervisors in improving the quality of education. Literature research is carried out by searching online for primary literature in the form of journal articles and other literary sources, which have valid criteria and have a good reputation on the topic under study. Meanwhile, content analysis was carried out on various scientific articles related to the topics studied. The results of the study show that educational supervisors are a component that has an important role in improving the quality of education. The role of educational supervisors is very strategic in improving the quality of education with the tasks they carry, including fostering, guiding, monitoring, supervising, evaluating, making reports, and following up on the results of supervision.